2006
DOI: 10.1111/j.1439-0418.2006.01065.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological effects of the natural products quassin, cinnamaldehyde and azadirachtin on Periplaneta americana (L.)

Abstract: The action of the plant products quassin, cinnamaldehyde and azadirachtin was examined using pharmacological and electrophysiological methods. All three substances inhibited the beat rate of the antenna-heart, with quassin causing a diastolic and cinnamaldehyde a systolic block. Quassin delayed and azadirachtin at first accelerated the frequency of action potentials in the heart muscle, but 5 · 10 )3 m of the latter compound degraded the spike pattern and decreased the heart rate. A typical prolongation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Similarly, Hertel et al . 39 found the plant essential oil components quassin and cinnamaldehyde to be neurologically active against P . americana .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Hertel et al . 39 found the plant essential oil components quassin and cinnamaldehyde to be neurologically active against P . americana .…”
Section: Introductionmentioning
confidence: 99%
“…The active compounds found in extracts of Azadirachta indica are Azadirachtin and Nimbim which have been reported to have toxic effects on insects [21] . The Azadirachtin displays neurotoxic effects on insects by altering the functions of the central nervous system (CNS) through inhibiting the excitatory cholinergic transmission and blocking the calcium channels partly [22,23,24] .…”
Section: Discussionmentioning
confidence: 99%
“…quassin (a triterpenoid from Quassia amara (L.), and cinnamaldehyde (an organic compound from Cinnamomum cassia [Nees & Nees) Presl.]. These studies demonstrated that physiological effects of these allelochemicals do not ease the primary insecticidal actions [14]. Mode of action of these two products however needs further studies as they can rather act as repellent only.…”
Section: Introductionmentioning
confidence: 95%